Self-Reflective Project in the EFL Online Class for Increasing Student Talk Time Using Cooperative Learning Method - Ade Irma Mentari; Deli Nirmala (Anuva: Jurnal Kajian Budaya, Perpustakaan, dan Informasi, 2020)
The pandemic of Covid19 causes teaching learning activities to be carried out online. This makes the teacher and students’ interactions limited on the screen. Through self-reflection project, it has been found that students’ engagement in class needs to be improved. Cooperative learning method was used to increase student talk time during the class. The data were four videos of the online class and the form of self-reflective project. Each video contained one lesson with its aim. The results showed that there was an increase in student talk time. Students became more active and engaged when participating in online classroom discussion. The teacher also produced less language production since the students played a role as the leader of the discussion who could make up particular rules during the discussion to create fun atmosphere. Students also became more creative and confident when sharing their ideas.